Directive Multiband Antenna Based on Rectangular Loop Array and Dumbbell-Shaped Slot Radiator - Jose Alfredo Tirado-Mendez (MDPI AG, 2021)
In this article, a combination of rectangular loop array and slot radiator for multiband applications is presented. The antenna is configured by arranging, concentrically, a set of rectangular loop radiators excited by electromagnetic coupling provided by a dumbbell slot. The size of the loops is calculated to obtain the desired resonant frequencies, which are almost independent of the adjacent rings. The exciting slot is designed to operate in a wideband frequency range to cover the upper desired resonance. In addition, to obtain directive radiation patterns, a reflector shaped like a box is introduced, giving a stable gain, radiation pattern shape, and port matching at the selected frequencies. The configuration presents great results, since to the authors’ knowledge, even a similar configuration given in the open literature presents some disadvantages compared to this one; moreover, not just any structure can be employed as the resonating elements, obtaining multiband behavior at the same time.